Hubungan Islam-Barat: Mungkinkah Ada Jalan Pemulihan - Salleh, Kamarudin (Jurnal Usuluddin, 2004)
The article intends to disclose the trends and patterns of relationship between Islam and the West since the beginning of the contact of both of the civilizations. To get a comprehensive perspective, the study firstly highlights the earliest historical facts of the relationship of Islam and Christianity (West). Secondly, presents the time of peace, harmony and mutual support which benefits much these two great civilizations. Thirdly, discusses the era of confrontation and war that lasts for centuries to these days. Finally, presents suggestions to bridge the gap between the two civilizations, hopefully to bring them to terma that acceptable and applicable to the whole World especially Islam and the West.